PENERAPAN SANKSI PIDANA TERHADAP RESIDIVIS ANAK YANG BERKONFLIK DENGAN HUKUM - Azhari, M. Alvi; Shodiq, M.D.; Basuki, Basuki (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
The application of criminal sanctions against child recidivists who conflict with the law in the juvenile criminal justice system in Indonesia. The background of the study departs from the phenomenon of increasing cases of children who commit repeat crimes, giving rise to a debate about the effectiveness of the juvenile criminal justice system that promotes the principle of restorative justice. This study aims to analyze how law enforcement is carried out against child recidivists, how criminal sanctions are imposed, and the extent to which the application of these sanctions is able to cause a deterrent effect without neglecting the best interests of children. The research employs a normative juridical approach with descriptive analysis, reviewing positive legal norms, court decisions, and relevant literature on theories of punishment and law enforcement. The findings reveal that law enforcement against juvenile recidivists faces a dilemma between protecting children’s rights and the need to ensure deterrence. Judges tend to impose heavier sentences on juvenile recidivists, yet still consider the ultimum remedium principle. The effectiveness of law enforcement is influenced by legal substance, legal structure, and legal culture, thereby requiring synergy among law enforcement agencies, families, and society. This study concludes that the application of criminal sanctions on juvenile recidivists should be progressive and proportional, combining deterrence with rehabilitation and social reintegration. Therefore, specific legal provisions on handling juvenile recidivists are necessary, alongside consistency from law enforcement officers in applying restorative justice principles to prevent children from re-engaging in criminal acts